Reimagining Tradition: Faisal Kamandobat and the Fusion of Islamic Values, Poetry, and Contemporary - Fiandini, Nabilla P. (Universitas Islam Internasional Indonesia, 2025)
Discourses on globalization, contemporary art and tradition often revolve around power dynamics, positioning them in binary terms of domination or emancipation. This paper proposes an alternative framework that moves beyond power relations, emphasizing the role of Bildung—a process of cultural and intellectual formation—in understanding the interaction between these forces. Through a critical analysis of Faisal Kamandobat's artistic practice, the paper argues that globalization, contemporary art and tradition are not opposing forces, but rather interconnected elements that shape cultural and artistic expression. Kamandobat's approach to art, which is deeply rooted in the pesantren tradition, shows how tradition can be reinterpreted through a modern and cosmopolitan sensibility. By exploring Bildung as a conceptual lens, this study reveals how culture functions as a living and evolving entity that bridges the past and the present. Ultimately, Kamandobat's work demonstrates that artistic practices can serve as spaces for creating meaning, resilience, and dialogue, rather than mere contestations of power.